STUDY OF CDA DURING SELENA GOMEZ'S DISCOURSE ON YOUTUBE - Rosmaria (PT. Anagata Sembagi Education, 2024)
Critical Discourse Analysis (CDA) pertains to the examination of language or linguistic usage. The objectives of this investigation were twofold: firstly, to identify the types of CDA evident in Selena Gomez's speeches, and secondly, to delineate the social cognition apparent within her speeches. The researcher employed Teun A. Van Dijk's (1998) Critical Discourse Analysis theory as the theoretical framework. Employing qualitative and descriptive methodologies, this study aimed to depict and scrutinize the data. The analysis primarily focused on dissecting the critical discourse present in Selena Gomez's speech texts. Through this analysis, three categories of CDA elements were identified in Selena Gomez's speeches: firstly, thematic elements, comprising a single category; secondly, syntactic style elements, subdivided into five categories, namely Persuasion, Impression Management, Attribution, Cohesion, and Pronoun usage; thirdly, semantic style elements, which were further categorized into Background and Detail, as well as Presupposition; and fourthly, schemata, classified into three segments: the opening section, the content, and the closing section. Additionally, several elements contributing to social cognition were discerned, including person schemas, self-schemes, and role schemes